EKSPLORASI FUNGI MIKORIZA ARBUSKULA INDIGENOS PADA ARENGA PINNATA MERR DI LAHAN PASCATAMBANG - Shaleha Istiqamah Samal; Irdika Mansur; Ahmad Junaedi (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Mining activities have a positive impact that can generate income for the state, but the activities also cause negative impacts in the form of soil damage, vegetation and animal losses to disrupt the ecosystems. Therefore, it is necessary to carry out a reclamation with revegetation using local plant species. PT Berau Coal has conducted revegetation using a local sugar palm plant (Arenga pinnata). The success of sugar palm plant growth in post-mining reclamation land is influenced by several factors, one of it is the symbiosis of the arbuscula mycorrhizal fungi (AMF) with the sugar palm planted by PT Berau Coal. The purpose of this study was to determine the diversity of indigenous spores in the arenga rhizosphere and root colonization of sugar palm plants. Identification of the AMF diversity was carried out by observing the soil taken from the palm rhizosphere with a depth of 0-20 cm and 20-40 cm. Isolation of spores using the wet pouring technique method with centrifuges and AMF spores were identified using the INVAM methods. The observation of AMF colonization on plant roots was carried out through the root staining technique with the Clapp modification method. The results showed that the AMF spores were found in 3 AMF genera at the observation site, namely genus Glomus (15 sp), Acaulospora (3 sp), and Gigaspora (1 sp). The highest spore abundance is genus Glomus sp at a soil depth of 0-20 cm. The AMF structures found colonizing the roots of sugar palm plants are hyphae, vesicles, and spores.